Energy-Saving Glazing Solutions: Design and Evaluation of Polarization-Based Mechanical Dimming Windows - Li Junfei; Luo Qian (E3S Web of Conferences)
Modern architecture increasingly integrates amorphous, inorganic, non-metallic, and transparent glass in the construction of high-rise buildings, fueled by the proliferation of social technology. Ordinary glass doesn't allow for subjective adjustment of its light transmission intensity and direction angle. Direct sunlight at noon, shining through an ordinary window, increases eye fatigue and visual loss due to its high intensity, resulting in adverse reactions like dry eyes and tears. To mitigate the negative effects of unsuitable light on people's lives, an adjustable light transmission glass window with directional angles is necessary for societal use. This paper uses a numerical simulation to investigate the correlation between the angle of polarization and the luminous flux of polarized glass windows, providing valuable insights for designing light transmission structures, bridging the knowledge gap on polarization principles in glass windows, and offering significant theoretical and practical implications for glass window manufacturers.